The Role of Bank Liquidity in Activating Investment in Iraq – An Analytical Study on the Bank of Baghdad - Karim, Muntaha Mohammed; Mushib, Jasim Mohammed (Journal of Economics and Administrative Sciences, 2024)
Purpose: To identify the size of cash credit granted by commercial banks and to clarify the role of banking liquidity in promoting investment in Iraq for the period (2014-2023).Theoretical Framework: The research addressed the role of banking liquidity in promoting investment for the period (2014-2023), and the problem lies in how to enhance the role of banking liquidity in stimulating investment.Design/Methodology/Approach: The researcher relied on the deductive approach and conducted a descriptive analysis using the measurement tool (E-views 12) to measure bank liquidity in enhancing bank credit.Results: The bank succeeded in adopting a strategy to expand its banking services locally and internationally, in line with regulatory standards and controls.Research, practical and social results: Banking liquidity plays a pivotal role in stimulating investment in developing economies such as Iraq, as banking liquidity is a fundamental factor in the stability of financial markets. The scientific and social importance of the research is highlighted by its focus on the role of banking liquidity and its impact on investment in Iraq.Originality/Value: The originality of the research is evident in helping economic decision-makers understand the effects of exchange rate fluctuations on the Iraqi economy and thus enabling them to make sound decisions regarding the financial policies needed to support the economy in the face of fluctuation risks. By studying banking liquidity, appropriate economic and banking policies can be identified to enhance the investment environment and reduce dependence on oil revenues.